2015
DOI: 10.1007/s10238-015-0372-3
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis viruses exploitation of host DNA methyltransferases functions

Abstract: Hepatitis B virus (HBV), hepatitis C virus (HCV) and Delta (HDV) infections are a global health burden. With different routes of infection and biology, HBV, HCV and HDV are capable to induce liver cirrhosis and cancer by impinging on epigenetic mechanisms altering host cell's pathways. In the present manuscript, we reviewed the published studies taking into account the relationship between the hepatitis viruses and the DNA methyltransferases proteins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 113 publications
(147 reference statements)
0
7
0
Order By: Relevance
“…We found that HBV suppressed NFAT5 expression by inducing hypermethylation of the AP1-binding site in the NFAT5 promoter. Though HBV doesn’t encode any methylases, however HBV infection can stimulate the overexpression of DNMTs, particularly DNMT1, DNMT3A and DNMT3B [ 25 ]. We speculate the overexpression of DNMTs may result in the hyper-methylation of the AP1-binding site in the NFAT5 promoter.…”
Section: Discussionmentioning
confidence: 99%
“…We found that HBV suppressed NFAT5 expression by inducing hypermethylation of the AP1-binding site in the NFAT5 promoter. Though HBV doesn’t encode any methylases, however HBV infection can stimulate the overexpression of DNMTs, particularly DNMT1, DNMT3A and DNMT3B [ 25 ]. We speculate the overexpression of DNMTs may result in the hyper-methylation of the AP1-binding site in the NFAT5 promoter.…”
Section: Discussionmentioning
confidence: 99%
“…MTases have been found in viruses, for example, LM21 prophage in Sinorizhobium [ 51 ] or the methyltransferase domain in rhinovirus and coronavirus that targets RNA cap [ 52 , 53 ], and ebolavirus that targets adenosine in RNA [ 54 ]. One mechanism exploited by some viruses is to induce the upregulation of mRNA of DNMTs in hepatitis, cirrhosis, and hepatocellular carcinoma, observed in the presence of hepatitis B virus [ 55 , 56 ]; Epstein Barr virus in gastric cancer [ 57 , 58 , 59 ]; herpesvirus LANA, in Kaposi’s sarcoma [ 60 ]; and interestingly in lymphoid cells, infected by human immunodeficiency virus 1 [ 61 ].…”
Section: Dna Methyltransferasesmentioning
confidence: 99%
“…The methylation landscape of HCV-positive HCC tissues differs from non-tumor controls and a correlation between HCV infection and aberrant methylation of genes such as CDKN2A (cyclin-dependent kinase inhibitor 2A), CDH1 (cadherin 1), SOCS1 (suppressor of cytokine signaling 1), RASSF1A (Ras associated domain family member 1), APC (adenomatous polyposis coli protein), GSTP1 (glutathione S-transferase Pi 1), STAT1 (Signal transducer and activator of transcription 1), and PRDM2 (PR/SET domain 2) in HCV-positive HCC has been established. Hampered expression of these genes contributes to cancer by promoting cell proliferation, mobility and invasion, and immune evasion [ 27 , 29 , 81 , 82 , 83 , 84 ]. The core protein seems to be implicated in HCV-induced DNA methylation because DNMT1 and DNMT3B levels were enhanced in HCV core protein expressing HepG2 cells and in Huh-7 cells compared to control cells [ 27 , 28 , 29 , 30 ].…”
Section: Oncoviruses and Host Cell Dna Methylationmentioning
confidence: 99%
“…Comparing the DNA methylation profile of HBV-associated HCC and HBV-negative tumors or healthy adjacent liver tissue, HBV-infected and non-infected cells, and HBx transgenic mouse model and control mice disclosed differentially methylation. Several cellular promoters were hypermethylated in the presence of HBV or HBx, including the promoters of the genes encoding cyclin-dependent protein kinases inhibitors p21 CIP1/WAF1 ( CDKN1A ), p14 ARF ( CDKN2A ) and p14 INK4B ( CDKN2B ), cadherin 1, RASSF1A, the spleen associated tyrosine kinase SYK ( SYK ), GSTP1, the protein phosphatase 1 regulatory subunit 13B ( PP1R13B ), the tumor promotor p53 binding protein 2 ( TP53BP2 ), and insulin like growth factor binding protein 3 ( IGFBP3 ) [ 52 , 53 , 82 , 84 , 133 , 134 , 135 , 136 , 137 , 138 ]. These proteins are involved in cell cycle control, apoptosis, migration and invasion, indicating that HBV-induced silencing of these genes play a role in HCC.…”
Section: Oncoviruses and Host Cell Dna Methylationmentioning
confidence: 99%